Trade and developing countries - Morton, Kathryn; Tulloch, Peter (London : Croom Helm ; The Overseas Development Institute, 1977)
This book takes a look at the role of trade in development, and consider the range of policy choices which follow from them for developing countries.
Includes index.
Bibliography: p. 351-356.
ijb, 15/01/2019
Loans
Keywords: Developing countries